Effects of Fish Farming on Sediment, Water Quality and Plankton Communities in Barobo Coastal Waters in Lianga Bay, Surigao Del Sur, Philippines (Proceedings International Conference on Fisheries and Aquaculture, 2023)
The study was conducted to establish the effect of fish farming on plankton communities, water quality and sediment in Barobo Coastal Waters in Lianga Bay Philippines. Plankton, water, and sediment samples were collected during northeast monsoon period (November, December, and February) within the fish farms; transition zone (in-between fish farm and outside) and outside the mariculture zone. Two stations were established per zone. Results showed that a total of 245 taxa, 66 genera and 90,532 individuals of phytoplankton, while zooplankton had 306 taxa, 192 genera and 10,984 individuals were recorded across sampling stations for the entire sampling periods. There were no significant differences except for abundance/richness noted on the diversity of both phytoplankton and zooplankton communities between stations indicating that mariculture activities have no effects on the plankton communities. For the water quality parameters, water temperature, salinity, ammoniacalN, dissolved organic phosphorous and potassium did not vary significantly (p>0.05) while pH, transparency, velocity, DO and TSS vary significantly (p
Keywords: Mariculture; spatial distribution; physicochemical parameters; fish farm; plankton